IMPACT ASSESSEMENT OF SEWERAGE DRAIN ON TUBEWELL WATER QUALITY USING MT3D MODEL - Alvina Shabbir; M. Arshad; A. Shabbir; A. Shakoor; I. Ahmad (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2015)
In last few decades, the demand of fresh water is rising magnificently due to rapid increase in population and food demand. A large quantity of groundwater is being used for irrigation due to shortage of surface water. In Pakistan the availability and quality of groundwater has been affected due to rapid urbanization and over exploitation. This research was conducted to assess the impact of sewerage drain at Jaranwala Drain on groundwater quality and evaluate the rate at which drain is deteriorating the groundwater quality. MODFLOW and MT3D models were used to calculate concentrations for different time intervals in aquifer at the end of year 2014. The results showed that the concentration of 723 mg/l was travelled 320 m towards pumping well for simulation time of 35 days in all three layers. After 1096 days of simulation, the travelled distance towards the pumping well was 1000, 970 and 920 m with concentration of 7020, 5630 and 5120 mg/l in the first, second and third layer, respectively. It was concluded that the horizontal movement of the concentration was very high as compared to the vertical movement. It was also concluded that if sewerage drain is passing near agricultural land then tubewell installation on two kilometers or away from drain is safe to avoid the contamination of tubewell water.